THE STEREOSPECIFIC SYNTHESIS OF ALAHOPCIN - Baldwin, J; Adlington, R; Godfrey, C; Gollins, D; Schofield, C (1991)
The first stereospecific synthesis of the naturally occuring dipeptide antibiotic, alahopcin, starting from (L-aspartic acid is described. © 1991.